Pengembangan Pembuatan Laporan Keuangan Dengan Ms. Excel Pada UMKM: Menuju Manajemen Keuangan Yang Profesional - Suryanti, Nunuk; Prabowo, Andri Eko; Suyono, Akhmad; Pratiwi, Hafsanah Eka (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The weakness of MSMEs in managing finances is characterized by unsystematic recording of business transactions. The development of financial reports using Ms Excel aims to make it easier for MSMEs to make financial reports to make decisions. The development design used is ADDIE. The research sample was taken from 15 MSMEs engaged in production, so the sampling technique used purposive sampling technique. The results showed an average overall item score of 0.876 (88%), meaning that the use of Ms Excel for financial reports is included in the criteria for very practical use. The effectiveness score of 0.864 (86%) means that the use of Ms. Excel for financial reports is included in the criteria very effective